Consumers’ insights into sex appeal in advertising An Exploratory study in context of Pakistani millennials Consumers - Ashraf, Awais (2022)
Sexual appeals in advertising are very prevalent worldwide. According to D'Emilio and Freedman (1989), contemporary consumerism is frequently marketed as satisfying sensual dreams and cravings. Despite its popularity, sexual appeal is always subject to disagreement and cultural sensitivity. The effectiveness and consumer attitudes toward sexual appeal have been the subject of several research, but little is discovered about the perspectives of Pakistani consumers on sexual appeal. This paper looks into how Pakistani millennial consumers perceive what is considered to be a sexual appeal, how brand endorsers are portrayed in sexual adverts, and how erotic appeal affects consumption behavior. In-depth interviews were conducted among ten participants aged 25-40 using a qualitative (inductive) approach. Data were collected via convenience sampling and analyzed thematically. The results revealed several overarching categories of sexual appeal. Physical characteristics of models and sexual innuendo were the most frequently mentioned categories in establishing a sexual appeal in ads. Other categories include facial expressions, erotic celebrity images, exposure to skin, style of clothing, sexual behavior of the model, contextual characteristics, and text. It was further discovered that many people find the sexual objectification of brand endorsers offensive and degrading. However, a smaller number of male participants think it is creative and funny. Additionally, findings indicate that the sexual objectification of models is against Pakistani cultural norms and encourages immorality and unrealistic standards in society. When appropriate to the product context, both sexes prefer a mild sexual appeal in addition to an emphasis on the practical benefits of the product to drive the purchase decision. In contrast, the overt use of sexual appeal prompted a boycott of products. The findings help marketing practitioners understand how sexual appeal can be utilized in Pakistani advertisements. Research on the sexual appeal of advertisements in Pakistani literature has primarily been quantitative. The present research fills a knowledge gap by using a qualitative approach and offer a framework for further research in this area.